Cyberplagiarism webliography. References to academic cyberplagiarism on the internet - Jaume Sureda; Rubén Comas; Mercè Morey (Digithum, 2008)
This article provides references to the documentation sources available on the internet, which may give interested readers a deeper insight into aspects of the multi-faceted issue of academic plagiarism in the student community.With that aim in mind, this paper is divided into six sections. The first provides information on research groups and centres working on the issue of plagiarism. The second gives references to academic journals focusing directly on the issue of academic plagiarism, and some others which publish articles on that subject regularly. The third refers to conferences and events aimed at analysing this phenomenon. The next two sections provide bibliographies and studies on plagiarism among students. The last section refers to documentary sources on various strategies for countering plagiarism.